PENGUATAN SINYAL JARINGAN KOMPUTER DI AREA PERKEBUNAN - Siregar, Simon; Suchendra, Devie Ryana; Kemala, Sherina Vega; Kusumaningrum, Widya Wahyu; Hasanah, Fadhillah Nur; Khair, Fahmi Pratama (LPPM Universitas Bina Bangsa, 2025)
Signal strengthening in the network at the Gambung Tea and Quinine Research Center (PPTK) is crucial to support research activities and daily operations. The location of PPTK Gambung, situated in a mountainous area, often faces issues of weak and unstable signals, hindering the efficiency of communication and access to information. This research aims to analyze various factors affecting signal quality in the area and to implement effective strategies to enhance signal strength. The research methodology involves field surveys, signal intensity measurements, and the installation of Access Points at key locations. The results indicate significant improvements in signal stability and strength, directly contributing to increased productivity and work efficiency at PPTK Gambung. The implementation of these strategies is expected to serve as a reference for improving signals in other remote locations with similar conditions